Downscaling climate-model output in mountainous terrain using local topographic lapse rates for hydrologic modeling of climate-change impacts. (4th March 2018) - Praskievicz, Sarah
Abstract: One of the challenges in using general circulation model (GCM) output is the need to downscale beyond the model's coarse spatial grid for use in hydrologic modeling of climate-change impacts. In mountainous terrain, using elevation as a primary control on temperature and precipitation at the local scale provides the potential for topographic variables to be used to adjust climate-model output. Here, local topographic lapse rates (LTLR) were estimated from gridded climate data for the Pacific Northwest of the United States and used to downscale GCM output. Skill scores were calculated for the LTLR-downscaled climate-model output relative to an existing set of model output downscaled using the established statistical downscaling technique of localized constructed analogs (LOCA). The results indicate that the LTLR method performs well in the mountainous study region relative to the LOCA method. LTLR downscaling offers a promising method for downscaling climate-model output in regions in which elevation strongly controls climate, particularly for studying impacts of future climate change on water resources.